Social Transformation and Education: Empowerment of the Wedegan Hamlet Community through Education and Religious Programs - Jamaluddin Akbar; Zainul Arif; Ulya Darojah; M. Khodimul Wahib (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Rural communities frequently encounter structural challenges related to limited educational access, declining social participation, and weakened community institutions. This study examines a community empowerment initiative implemented in Wedegan Hamlet, Sambikerep Village, Nganjuk Regency, Indonesia, focusing on the integration of education and religious programs as instruments of social transformation. The program adopted a Participatory Action Research (PAR) framework that positioned community members as active collaborators in identifying local challenges, designing interventions, and implementing solutions. Program activities included the revitalization of mosque-based religious programs, non-formal educational tutoring for children, women’s counseling and empowerment initiatives, and youth engagement through tambourine-based religious arts training. Empirical evaluation was conducted through participatory observation, informal interviews, and continuous monitoring of participation patterns among program beneficiaries. The findings indicate measurable improvements in community participation in religious activities, stronger parental involvement in supporting children’s learning, and increased youth engagement in collaborative cultural activities. These outcomes illustrate how integrated educational and socio-religious initiatives can strengthen social cohesion, enhance community participation, and stimulate grassroots social transformation in rural contexts. The study highlights the importance of participatory empowerment approaches in fostering sustainable community development.